Relationship between texture of gels and flavour release - Koliandris, Andreas (2009)
To provide further insight into the relationship between the structure of hydrocolloid solutions and gels and perception of taste and flavour, solutions of gelatin and locust bean gum, and gels prepared from mixtures of (a) high acyl and low acyl gellan (b) carrageenan and locust bean gum were studied. Both solutions contained sodium chloride and the gels were flavoured with ethyl butyrate. The gels were classified from rheological measurements into 3 categories: strong/brittle, intermediate and soft/elastic. Volatile release was measured by monitoring nose space volatile concentration during consumption using Atmospheric Pressure Chemical Ionisation-Mass Spectrometry (APCI-MS). In addition headspace measurements were performed with APCI-MS. The headspace concentrations did not exhibit significant differences between the gels systems but the release of ethyl butyrate in-nose was affected by the matrix, showing a higher intensity for the more brittle gels containing high levels of low acyl gellan. The release of Na' following a two bite compression was monitored by the use of an ion specific electrode. The more brittle gels containing high levels of low acyl gellan and high amount of K-carrageenan exhibited significantly higher release of Na'. Strain at break correlated inversely with salt release (r2=-0.87) and nose space volatile concentration (r2=-0.55). In a later stage gelatin was added (1-5%) in the previous mixtures of HA-Gellan and LA-Gellan (constant polysaccharide concentration of 0.6%). The rheological analysis of the gels yielded different behaviour of the gels. At low levels of LA-Gellan the rheological data can be explained by polymer blending laws. At higher levels of LA-Gellan, development of elastic behaviour from the previous brittle gels observed does not fit polymer blending law theory. Flavour release during diffusion experiment showed that at 37°C the gels containing gelatin exhibited higher salt release. Temperature sweeps have shown that a drop of G' is observed around 27-28° C indicating that the gelatin present in the mixture is melting. However the level of the drop of G' indicates that the continuous phase of the gel composite was the gellan system. Volatile release was measured by monitoring nose space volatile concentration during consumption using Atmospheric Pressure Chemical Ionisation-Mass Spectrometry (APCI-MS) but showed no significant differences between the different gels. Headspace experiments performed at different temperatures showed that the gels containing high amounts of gelatin when compared to control gels that contained 0% gelatin exhibited higher release of ethyl butyrate. To mimic the mixing of gelatin with saliva after melting, gelatin solutions at 50°C containing salt were mixed with water. Even at high concentrations (30%) of gelatin mixing efficiency and release was very efficient. In contrast when locust bean gum solutions containing salt were mixed with distilled water it was found that both salt release and mixing efficiency decreased at polysaccharide concentrations above c*. It is concluded that the intensity of flavour perception in hydrocolloid solutions and gels is dominated by the release of the tastant. In solutions this is favoured by good mixing behaviour between the hydrocolloid solution and saliva and in gels by a low strain at break. A gelatine replacement should not only show melt in the mouth behaviour but good mixing between the melted gelatin and saliva. It was shown that thermal processing at 121°C induced deacetylation of HA-gellan at much lower pH than would normally be needed in a typical deacetylation process. Therefore new textures can be achieved through deacetylation through heat processing. When gels which were prepared by deacetylation by heat processing were compared with blends that had an equivalent acyl content different textures were obtained even though the Young's modulus was very similar at the same total acyl content. The implications of this work for gelled petfood products is discussed.